Delayed recovery from general anaesthesia associated with pre‐existing neurological disease in a horse. Issue 4 (26th November 2019) - Lord, Samuel; Hahn, Caroline; Pollock, Patrick J; Duncan, Juliet Clare
Abstract : A seven‐year‐old gelding presented for surgical management of right‐sided olecranon bursitis. Preanaesthetic examination revealed a right‐sided head tilt which had been present since birth. General anaesthesia and surgery went smoothly without incident. Recovery was prolonged and the horse made no attempt to stand despite regaining motor function consistent with recovery from general anaesthesia. Increasingly loud auditory stimuli and mild physical stimuli yielded no attempt to move into sternal recumbency or stand. After over two hours in the recovery box an equine neurologist suggested a diagnosis of vestibular disease and proposed that without a horizon the horse would not be able to orientate itself, therefore advising that the horse be shown the horizon. The outside recovery box door was opened allowing the horse to see the horizon, on which the horse made an immediate coordinated attempt to stand, standing successfully on its first attempt.